Ultrasound Detection of Myocardial Ischemic Memory Using an E-Selectin Targeting Peptide Amenable to Human Application - Xiaoping Leng; Jianjun Wang; Andrew Carson; Xucai Chen; Huili Fu; Susanne Ottoboni; William R. Wagner; Flordeliza S. Villanueva (Molecular Imaging)
Vascular endothelial leukocyte adhesion molecules, such as E-selectin, are acutely upregulated in myocardial ischemia/reperfusion and are thus “ischemic memory” biomarkers for recent cardiac ischemia. We sought to develop an ultrasound molecular imaging agent composed of microbubbles (MBs) targeted to E-selectin to enable the differential diagnosis of myocardial ischemia in patients presenting with chest pain of unclear etiology. Biodegradable polymer MBs were prepared bearing a peptide with specific human E-selectin affinity (MB ESEL ). Control MBs had scrambled peptide (MB CTL ) or nonspecific IgG (MB IgG ). MB ESEL adhesion to activated rat endothelial cells (ECs) was confirmed in vitro in a flow system and in vivo with intravital microscopy of rat cremaster microcirculation. Ultrasound molecular imaging of recent myocardial ischemia was performed in rats 4 hours after transient (15 minutes) coronary occlusion. MB ESEL adhesion was higher to inflamed versus normal ECs in vitro; there was no difference in MB CTL or MB IgG adhesion to inflamed versus normal ECs. There was greater adhesion of MB ESEL to inflamed versus noninflamed microcirculation and minimal adhesion of MB CTL or MB IgG under any condition. Ultrasound imaging after injection of MB SEL demonstrated persistent contrast enhancement of the previously ischemic region. Videointensity in postischemic myocardium after MB ESEL was higher than that in the nonischemic bed (11.6 ± 2.7 dB vs 3.6 ± 0.8 dB, p < .02) and higher than that after MB CTL (4.0 ± 1.0 dB, p < .03) or MB IgG (1.7 ± 0.1 dB, p < .03). MBs targeted to E-selectin via a short synthetic peptide with human E-selectin binding affinity enables echocardiographic detection of recent ischemia, setting the stage for clinical myocardial ischemic memory imaging to identify acute coronary syndromes.